2021
DOI: 10.5811/westjem.2020.9.47840
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Temporal Characteristics of Housing Needs in an Urban Emergency Department

Abstract: Introduction: Our objective was to determine the proportion of patients in our emergency department (ED) who are unhoused or marginally housed and when they typically present to the ED. Methods: We surveyed patients in an urban, safety-net ED from June-August 2018, using a sampling strategy that met them at all times of day, every day of the week. Patients used two social needs screening tools with additional questions on housing during sampling shifts representing two full weeks. Housing status was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…The potential need is significant: our finding that 25% of patients were worried that they may not have stable housing in the next 2 months is similar to the findings from a study conducted in an urban ED in Oakland, California. 30 Differences in performance between 2 screening questions examined in this study are consistent with past research showing that various housing-related screening questions used in health care settings were not necessarily interchangeable. 31 In a prior study, 20 our research group examined the performance of a broad array of variables in identifying future homelessness and found that variables related to patient past homelessness had higher PPVs than other individual-level variables, such as those related to medical issues, behavioral health, and other social factors.…”
Section: Discussionsupporting
confidence: 88%
“…The potential need is significant: our finding that 25% of patients were worried that they may not have stable housing in the next 2 months is similar to the findings from a study conducted in an urban ED in Oakland, California. 30 Differences in performance between 2 screening questions examined in this study are consistent with past research showing that various housing-related screening questions used in health care settings were not necessarily interchangeable. 31 In a prior study, 20 our research group examined the performance of a broad array of variables in identifying future homelessness and found that variables related to patient past homelessness had higher PPVs than other individual-level variables, such as those related to medical issues, behavioral health, and other social factors.…”
Section: Discussionsupporting
confidence: 88%
“…Survey administration, development, and validation is described in a prior manuscript. 32 The survey instrument used questions from two social needs screening tools: the Protocol for Responding to and Assessing Patient Assets, Risks, and Experiences (PRAPARE), developed by the National Association of Community Health Centers, 33 and the Accountable Health Communities (AHC) Health-Related Social Needs Screening Tool, developed by the Centers for Medicare and Medicaid Services. 34 The full survey instrument is available in Appendix A.…”
Section: Survey Developmentmentioning
confidence: 99%
“…Association of Social Needs and Housing Status Among Urban ED Patients The full results of the propensity score analysis were published in a prior manuscript; the distribution of scores grouped toward the middle suggested that the respondents and nonrespondents were similar with regard to baseline characteristics. 32…”
Section: Wormley Et Almentioning
confidence: 99%
“…While social medicine should be taught broadly, it is important for EM trainees in particular to have formal curricula on social risks and social needs, because the low-acuity medical patient with complex psychosocial comorbidities is more common in EM than anywhere in the house of medicine. 17,18 Further, it is important to own this mission as the purview of EM so that the specialty may standardize, peer review, and validate best practices in social medicine. 17,18 Training EM residents to identify and address adverse SDH and other public health challenges is an important step to improving the overall health of the population and reducing health and health care disparities in this country.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Further, it is important to own this mission as the purview of EM so that the specialty may standardize, peer review, and validate best practices in social medicine. 17,18 Training EM residents to identify and address adverse SDH and other public health challenges is an important step to improving the overall health of the population and reducing health and health care disparities in this country. 19,20…”
Section: Introductionmentioning
confidence: 99%